The problem of political socialization in ethnic groups - G. G. Khachatryan (Ассоциация независимых экспертов «Центр изучения кризисного общества» (in English: Association for independent experts “Center for Crisis Society Studies”), 2018)
Article deals with the problem of political socialization in ethnic groups. The questions of the formation of political views within the family, schools with ethno-cultural component, cultural centers are treated. The issue of fragmentation of ethnic communities and the existence of mechanisms that target disintegration is addressed.